2019
DOI: 10.15171/hpp.2019.34
|View full text |Cite
|
Sign up to set email alerts
|

Profile of drug users in the residential treatment centers of Tehran, Iran

Abstract: Background: The current study aimed at determining the pattern of drug dependence and its related factors in mid-term residential treatment centers (MTRCs). Methods: The current cross-sectional study was conducted on all drug dependent people residing in MTRCs of Tehran, Iran, who were voluntarily seeking treatment from April to August, 2018. Required data were collected through face-to-face interviews. Drug dependence was categorized into four groups: soft opioids, hard opioids, methamphetamine, and combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The Iranian National Mental Health Survey (IranMHS) estimated the prevalence of any substance use disorder to be 2.8% in the Iranian general population [9]. Although it was previously estimated that more than 20% of PWUD had used drugs through injection in the last 12 months [10], recent studies have shown that the figure has decreased to about 3% [11,12]. In Iran, drug use and injecting drug use are known as the main risk factors for HIV and HCV [13][14][15][16][17]; therefore, the country has adopted extensive harm reduction measures to control blood-borne infections among PWID for more than a decade.…”
Section: Introductionmentioning
confidence: 99%
“…The Iranian National Mental Health Survey (IranMHS) estimated the prevalence of any substance use disorder to be 2.8% in the Iranian general population [9]. Although it was previously estimated that more than 20% of PWUD had used drugs through injection in the last 12 months [10], recent studies have shown that the figure has decreased to about 3% [11,12]. In Iran, drug use and injecting drug use are known as the main risk factors for HIV and HCV [13][14][15][16][17]; therefore, the country has adopted extensive harm reduction measures to control blood-borne infections among PWID for more than a decade.…”
Section: Introductionmentioning
confidence: 99%
“…Although opium dependence accounts for a large portion of Iran’s total opioid dependence, and about two-thirds of dependents and treatment centers’ clients are opium dependences or have experienced opium use at some point in their lives, 5 , 44 but few national and international studies have specifically addressed the treatment parameters of opium dependence. 25 , 40 In this study, the parameters values were estimated based on the available evidences and was presented an opium dependence treatment model.…”
Section: Discussionmentioning
confidence: 99%
“…Iran is a country highly exposed to this global problem due to its young population and geographical location. A study on the worldwide burden of disease in Iran (2010) indicates the increasing trends in drug abuse and the resultant mortality rates among Iranian youth in recent years 3,4. In general, unhealthy behaviors, such as tobacco, alcohol, and addictive substances, often begin in late adolescence and early young ages 5.…”
mentioning
confidence: 99%
“…A study on the worldwide burden of disease in Iran (2010) indicates the increasing trends in drug abuse and the resultant mortality rates among Iranian youth in recent years. 3,4 In general, unhealthy behaviors, such as tobacco, alcohol, and addictive substances, often begin in late adolescence and early young ages. 5 A study in Tehran showed an 11.8% prevalence of substance use among medical students.…”
mentioning
confidence: 99%